2010
DOI: 10.1021/cm101019p
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Nanotubes Formed from Ultrashort Amphiphilic Peptide I3K and Their Templating for the Fabrication of Silica Nanotubes

Abstract: Many de novo designed amphiphilic peptides capable of self-assembly and further structural templating into hierarchical organizations such as nanofibers and gels carry more than 10 amino acid residues. A curious question is now raised about the minimal size that is required for initiating amphiphilically driven nanostructuring. In this work, we show that ultrashort peptides I 3 K and L 3 K could readily self-assemble into stable nanostructures. While L 3 K formed spherical nanospheres with diameters of ∼10-15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(188 citation statements)
references
References 82 publications
8
180
0
Order By: Relevance
“…Ac-I 3 K-NH 2 molecules self-assembled in aqueous solution to form long nanofibers that tended to entangle with increasing peptide concentration [29]. At a relatively high concentration of 10 mmol/L, a self-supporting gel formed, but possessed weak mechanical properties with the storage modulus (G′) being 200-300 Pa. At lower concentrations typically below 4 mmol/L, peptide solutions were always freely flowing liquids, regardless of incubation time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ac-I 3 K-NH 2 molecules self-assembled in aqueous solution to form long nanofibers that tended to entangle with increasing peptide concentration [29]. At a relatively high concentration of 10 mmol/L, a self-supporting gel formed, but possessed weak mechanical properties with the storage modulus (G′) being 200-300 Pa. At lower concentrations typically below 4 mmol/L, peptide solutions were always freely flowing liquids, regardless of incubation time.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we have designed an ultrashort peptide amphiphile Ac-I 3 K-NH 2 , consisting of three consecutive hydrophobic Ile residues and a charged Lys residue, and found that it could readily self-assemble into long nanofibers in aqueous solution [29]. These nanofibers could entangle to form a network, thus reducing the fluidity of solution and finally resulting in hydrogelation at a concentration of 10 mmol/L (0.53%, w/v).…”
mentioning
confidence: 99%
“…In contrast, unordered structure dominates during the Ac-L 3 K-NH 2 self-assembly. With an increase in the number of hydrophobic residues, Ac-I 5 K-NH 2 and Ac-L 5 K-NH 2 have converged to nearly identical CACs at a lower value (Table 2) [47,[49][50][51][52][53][54][55]. The increase in hydrophobicity evidently induces the formation of β-sheet hydrogen bonding in the case of Ac-L 5 K-NH 2 [54].…”
Section: Critical Aggregation Concentration (Cac)mentioning
confidence: 96%
“…In comparison with other selfassembling peptides, the specific advantages of SLPs lie in their short length (typically less than 10 residues) and high solubility in aqueous solutions ( Table 1). As examples, ultrashort SLPs containing three or four residues such as Ac-IVD and Ac-IIIK-NH 2 have been found to readily selfassemble into long fibers in water [46,47]; A 6 K shows high solubility in water up to ~12 wt% and forms a nematic phase consisting of long assembled nanotubes at ~17 wt% [48]. Although some short FF-containing peptides (e.g., FF and KLVFFAE) can also form long tubes or fibers, they show poor water solubility and their self-assembly in aqueous solutions is usually realized by adding organic solvents such as 1,1,1,3,3,3-hexafluoro-2-propanol or acetonitrile [9,[35][36][37]70].…”
Section: Introductionmentioning
confidence: 99%
“…The nanobelts continue to grow, and the twists become more exaggerated. Only when there are enough aromatic pentapeptide molecules on the two edges of the lamellae, providing enough force to further twist them, do the edges of nanobelts fuse and disappear resulting in the formation of nanowires 16 . where λ nm is the wavelength of the first emission absorption peak of the corresponding sample 17 .…”
Section: Proposed Mechanismmentioning
confidence: 99%